Web-based Expedition Package System in Mail Processing Center PT. Pos Indonesia (Persero) Yogyakarta - Richki Hardi; Nanna Suryana; Naim Che Pee; Budi Sunaryo; Saiful Ghozy; Farah Farhana (Universitas Mulia, 2018)
At a shipping company or shipping service, that is, the central processing of PT. Pos Indonesia Yogyakarta, there are various kinds of problems that occur, for example, the issue of package delays or even the loss of a package that will be sent both while still at the branch office or while traveling. It can be caused due to poor service delivery or other services. To facilitate the company in overcoming the problems that often occur in package delivery and assist consumers in tracking the whereabouts of packages sent through the company, an expedition system will be applied, namely a system that functions to track or trace specific packages sent by consumers to the shipping company thus the consumer can quickly get information about the packages sent, when and where and how the condition of the box is located. And all existing branch offices of the company can be integrated into the system so that all operational activities of each branch will be recorded in the system database. Thus the author will examine how to make the package expedition system easy to apply for consumers, so consumers do not need to worry or go to the office to ask for the package.